2023
DOI: 10.3389/fragi.2023.1161814
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophic effects of intermittent fasting, calorie restriction and exercise: a review and annotated bibliography

Abstract: In the last decades, important progress has been achieved in the understanding of the neurotrophic effects of intermittent fasting (IF), calorie restriction (CR) and exercise. Improved neuroprotection, synaptic plasticity and adult neurogenesis (NSPAN) are essential examples of these neurotrophic effects. The importance in this respect of the metabolic switch from glucose to ketone bodies as cellular fuel has been highlighted. More recently, calorie restriction mimetics (CRMs; resveratrol and other polyphenols… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 296 publications
0
2
0
Order By: Relevance
“…Higher BDNF concentrations in the hippocampus have been associated with both improved cognitive function [48] and metabolic health [49]. Recently, many animal (rodent) studies have revealed that IF positively stimulates the production of BDNF in the hippocampus, cerebral cortex, and striatum and reduces cognitive deficits by enhancing neurotrophic support and suppressing the expression of pro-inflammatory cytokines [18,50,51].…”
Section: Discussionmentioning
confidence: 99%
“…Higher BDNF concentrations in the hippocampus have been associated with both improved cognitive function [48] and metabolic health [49]. Recently, many animal (rodent) studies have revealed that IF positively stimulates the production of BDNF in the hippocampus, cerebral cortex, and striatum and reduces cognitive deficits by enhancing neurotrophic support and suppressing the expression of pro-inflammatory cytokines [18,50,51].…”
Section: Discussionmentioning
confidence: 99%
“…The geroprotective effect of SIRT1 is regulated via p53, NF-κB, mTOR, PGC1α, and FOXO signal pathways [169][170][171]. Sirtuins are also required for caloric restriction-induced life span extension [171,172].…”
Section: Sirtuinsmentioning
confidence: 99%